Does defending affect adolescents' peer status, or vice versa? Testing the moderating effects of empathy, gender, and anti-bullying norms - Laninga-Wijnen Lydia; Malamut SarahT; Garandeau Claire F; Salmivalli Christina (Wiley, 2025)
This study examined bidirectional associations between students' bully-directed defending behavior and their peer status (being liked or popular) and tested for the moderating role of empathy, gender, and classroom anti-bullying norms. Three waves of data were collected at 4-5-month time intervals among 3680 Finnish adolescents (M-age = 13.94, 53.0% girls). Cross-lagged panel analyses showed that defending positively predicted popularity and, to a larger degree, being liked over time. No moderating effect of empathy was found. Popularity was more strongly predictive of defending, and defending was more strongly predictive of status among girls than among boys. Moreover, the positive effects of both types of status on defending were-albeit to a limited extent-stronger in classrooms with higher anti-bullying norms.